Salin-suri : panimulang pagmamapa ng mga larangan ng pag-aaral ng pagsasalin sa Filipinas : ikatlong sourcebook ng Sangfil - Zafra, Galileo S.; Sanggunian sa Filipino; National Commission on Culture and the Arts (Philippines) (Diliman : Sanggunian sa Filipino, UP Sentro ng Wikang Filipino ; Manila : National Commission for Culture and the Arts, 2009)
Guidelines on learning and doing translations in the Philippines.
Includes bibliographical references.
In Tagalog.
Keywords: Translating and interpreting -- Study and teaching -- Philippines